(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Domestic violenceis extremely complex vicious from of abuse, committed most often within fourwalls of the family or within a particular deep rooted power dynamic andsocio-economic structure, which do not allow even the recognition oracknowledgement of this abuse. A women may of any age, she may girl child,unmarried, married or elderly women including a widow or such women with whommen have marriage like relationship.